EFFECT OF CHOPPING STEP AND DRYING TECHNIQUE ON THE QUALITY OF ALKALI TREATED COTTONII (ATC) - Singgih Wibowo; Muhamad Darmawan; Arif Rahman Hakim; Seruni Marsella (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
A research related to the production of alkali treated cottonii (ATC) had been carried out in order to study the effect of chopping step and drying techniques on the quality of ATC produced. Four treatments were applied in the experiment, namely was copping before sun drying (treatment A); chopping after sun drying (B); chopping before mechanical drying (C); and chopping after mechanical drying (D). The quality parameters of ATC measured were gel strength, moisture content, viscosity, yield, and whiteness. The results showed that the quality of ATC was significantly affected by chopping step and drying technique, especially in ATC gel strength, viscosity and yield. However, the effect of chopping step and drying technique was insignificant to ATC moisture content and whiteness. Chopping seaweed before drying resulted in higher gel strength of the ATC but lower in yield, while chopping after drying tended to result in lower gel strength but higher viscosity and yield.